Subsequent yielding of polycrystalline aluminum after cyclic tension–compression analyzed by experiments and simulations. (15th March 2015) - Hu, Guijuan; Huang, Shihong; Lu, Damin; Zhong, Xianci; Li, Zhenhuan; Brocks, Wolfgang; Zhang, Keshi
Abstract: Subsequent yielding of polycrystalline aluminum after cyclic tension–compression is studied by both experiments and finite element simulations applying crystal plasticity. The directional hardening induced by pre-deformation is particularly emphasized. By means of a sub-model method, scale-bridging analyses of a specimen containing a ring-section constructed of a number of grains re-loaded in different ratios of axial tension and torsion are carried out, after cyclic tension–compression pre-deformation. Both the Chaboche rate-dependent constitutive relation and the crystal plasticity theory extended by introducing a back stress, which relates the mechanical behavior of polycrystalline aluminum at macroscopic scale and microscopic scale, are employed. The influences of different unloading loci, pre-loading directions and yield definitions on subsequent yield surfaces are investigated in detail by comparing computational and experimental results. The results show that the shape of subsequent yield surfaces and the "sharp corner" appearing at the front end of a yield surface are closely related to the tensile or compressive pre-loading direction and different yield point definitions. The subsequent yielding by re-loading obviously shows deformation-induced anisotropic hardening. The main characteristics of subsequent yield surfaces observed in experiments can be satisfactorily captured by the present crystal plasticity model with the introduction of a back stress.